2017
DOI: 10.1038/s41598-017-08928-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain plasticity following MI-BCI training combined with tDCS in a randomized trial in chronic subcortical stroke subjects: a preliminary study

Abstract: Brain-computer interface-assisted motor imagery (MI-BCI) or transcranial direct current stimulation (tDCS) has been used in stroke rehabilitation, though their combinatory effect is unknown. We investigated brain plasticity following a combined MI-BCI and tDCS intervention in chronic subcortical stroke patients with unilateral upper limb disability. Nineteen patients were randomized into tDCS and sham-tDCS groups. Diffusion and perfusion MRI, and transcranial magnetic stimulation were used to study structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 77 publications
5
53
0
Order By: Relevance
“…Although it could be argued that performing MI and MI during BCI activates different neural networks, it has been shown that they activate a common large and distributed cortical and subcortical network including motor, premotor, supplementary and posterior parietal cortex ( Marchesotti et al, 2017 ). From another new perspective, recent studies suggest that the transcranial direct-current stimulation increases MI-BCI accuracy ( Ang et al, 2015 ; Hong et al, 2017 ). In this way, it has been shown that tDCS applied on motor cortex and cerebellum ten minutes before right-hand MI enhanced the accuracy of a classifier trained with the related mu and beta spectral power ( Angulo-Sherman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it could be argued that performing MI and MI during BCI activates different neural networks, it has been shown that they activate a common large and distributed cortical and subcortical network including motor, premotor, supplementary and posterior parietal cortex ( Marchesotti et al, 2017 ). From another new perspective, recent studies suggest that the transcranial direct-current stimulation increases MI-BCI accuracy ( Ang et al, 2015 ; Hong et al, 2017 ). In this way, it has been shown that tDCS applied on motor cortex and cerebellum ten minutes before right-hand MI enhanced the accuracy of a classifier trained with the related mu and beta spectral power ( Angulo-Sherman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The structural and functional changes in neural substrates induced by MI-based training with transcranial direct current stimulation or transcranial magnetic stimulation provide further evidence for the induction of neuroplasticity that is essential for motor recovery (Hong et al, 2017;Johnson et al, 2018). Because the induction of plasticity by rehabilitation varies across subjects (Leamy et al, 2014;Vallence et al, 2015), subject-specific training sessions may be required.…”
Section: Neuroplasticity and Bci-driven Motor Rehabilitationmentioning
confidence: 99%
“…Voxel-wise CBF analysis and behavioural correlation [13]. (a) CBF of all the patients (tDCS and sham groups together) is lower especially in the ipsilesional hemisphere compared to the control at the baseline.…”
Section: Resultsmentioning
confidence: 99%